Effect of initial pH and substrate to inoculum ratio on the production of methane and hydrogen from food waste. (2023) - Deheri, Chinmay; Kumar Acharya, Saroj; Mishra, Ruby
Abstract: "Anaerobic co-digestion of food waste, cow dung, and sludge solution is experimented by varying the pH to produce hydrogen and methane as a source of renewable energy. The substrate to inoculum ratio (v/v) of 1:1(S1), 1:2(S2), 1:3(S3), 1:4(S4) and 1:5(S5) are investigated in separate fermentative and methanogenic reactors. A maximum hydrogen and methane concentration of 19.73% and 64.81% respectively are obtained in S3. The methane concentration of 53.67%, 64.81% and 59.64% is observed at the pH variation of 6.5, 7, and 7.5 respectively. The obtained result shows the substrate to inoculum ratio of 1:3 to be the optimal combination for the highest methane and hydrogen production during the anaerobic co-digestion process".